MENJADI PEMIMPIN TANGGUH DI ERA DIGITAL - Saiful Anwar; Sri Utaminingsih; Estiningsih Trihandayani; Muhamad Harry Subagio; Andri Lukmana; Faniya Putriani; Junita Hotnida Ambarita; Ripki Amiludin; Titi Santi Nugrahaeni (JPMUJ, 2025)
This community service program, entitled "Becoming a Leader in the Digital Era" aims to develop leadership skills and organizational abilities among students of SMK Sasmita Jaya 1 Pamulang. Through workshops and interactive sessions, this program is designed to equip students with the skills needed to become competent and innovative leaders in the digital era. This activity aims to provide insight into the characteristics of today's leaders who are collaborative, adaptive to change, and able to manage teams across generations and technologies and introduce the importance of utilizing digital data and information in making fast, accurate, and strategic decisions. This program also focuses on developing communication, management, and decision-making skills with an emphasis on real-world applications. The main objective of this program is to prepare students to be able to compete in the digital technology-based industrial world, where leadership is not only based on authority, but also competence and collaboration.